Heat shock protein patterns in the bovine ovary and relation with cystic ovarian disease - Velázquez, Melisa María del Luján (2010)
The present study was performed to determine how the development of cystic ovarian disease (COD) affecting the ovarian expression of heat shock proteins (HSP) in cows were expressing extrous cycles. HSP27, HSP60, HSP70 and HSP90 were evaluated in different ovarian components by Western blot and semiquantitative immunohistochemical analysis. Greater expression of the HSP27 gene was detected in the granulosa and theca cells of primary, secondary, tertiary and cystic follicles, with decreasing amount in atretic follicles. HSP60, HSP70 and HSP90 showed a similar pattern of immunostaining, with moderate gene expression in primary and secondary follicles, increased expression in tertiary and atretic follicles with the greatest gene expression in cystic follicles. HSP were also localized in the corpus luteum, corpus albicans, interstitial tissue and tunica albuginea. The relative amount of protein in the follicular wall of small and large healthy follicles and cystic follicles as analysed by Western immunoblot was consistent with the immunohistochemical data. We speculate that altered expression of HSP genes decreases apoptosis in the follicular wall and leads to the delayed regression of cystic follicles. This study supports earlier observations suggesting that aberrant HSP gene expression, observed in cells of the cystic follicles, is probably associated with the intra-ovarian component of COD pathogenesis.